Design and analyze the spatial movement maps of the displaced in 2014 in the Kurdistan Region of Iraq Cartographic study - jihad, ahmed mohamed (Journal of Social Sciences and Humanities, 2021)
The research deals with the phenomenon of spatial movement of the displaced in Iraq in 2014 and its impact on the organization of spatial them, and to know the reasons that led to the disparity of this distribution? And the implications of it? Are driving and attracting factors? By mapping immigration traffic from expulsion areas to attractions? A systematic analysis approach was adopted using GIS technology and its model was cartographic Displaced people in Kurdistan region were studied by preparing quantitative maps of the numbers of families from hot areas (Anbar, Sal ah Alden and Mosul), and came up with conclusions and recommendations for effective solutions to their problems and treatment. The importance of the research lies in the absence of a cartographic study of the phenomenon of migration in Iraq designed by computer in the representation of spatial indicators of the phenomenon studiedly.